2019
DOI: 10.1016/j.rmed.2019.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Sputum biomarkers during aspirin desensitization in nonsteroidal anti-inflammatory drugs exacerbated respiratory disease

Abstract: Background: Aspirin desensitization (AD) is an effective and safe therapeutic option for patients with nonsteroidal anti-inflammatory drugs (NSAIDs)-exacerbated respiratory disease (N-ERD). The mechanisms driving its beneficial effects remain poorly understood. Objective: To investigate the effect of long-term AD on clinical, biochemical and radiological changes in N-ERD patients. Methods: The study group consisted of twenty-three individuals with N-ERD who underwent AD, followed by ingestion of 325 mg aspirin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 47 publications
0
22
1
Order By: Relevance
“…Although the role of serum IgE is not well established in the natural progression of AERD, previous studies have reported high levels of IgE in patients with AERD in the absence of atopy and also as a response to staphylococcal superantigens . Interestingly, aspirin responders in this study—as well as in another study on aspirin treatment responders where IgE levels were reported—appeared to have lower IgE levels than aspirin nonresponders . Nonresponders were more likely to be African American.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…Although the role of serum IgE is not well established in the natural progression of AERD, previous studies have reported high levels of IgE in patients with AERD in the absence of atopy and also as a response to staphylococcal superantigens . Interestingly, aspirin responders in this study—as well as in another study on aspirin treatment responders where IgE levels were reported—appeared to have lower IgE levels than aspirin nonresponders . Nonresponders were more likely to be African American.…”
Section: Discussioncontrasting
confidence: 56%
“…27 Interestingly, aspirin responders in this study-as well as in another study on aspirin treatment responders where IgE levels were reported-appeared to have lower IgE levels than aspirin nonresponders. 10 Nonresponders were more likely to be African American. Several studies showed that African Americans tend to have higher IgE levels than Caucasians.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…With longer-term high-dose aspirin therapy, one proposed mechanism of clinical benefit is a reduction in PGD2 activity. 45,46 However, high-dose aspirin therapy does not appear to rectify the overall dysregulation in eicosanoid synthesis and MC homeostasis characteristic of AERD. The clinical benefit of daily high-dose aspirin in AERD appears to be independent of a reduction in MC activation and CysLT production.…”
Section: Therapeutic Implications MC Response During Long-term Aspirimentioning
confidence: 99%